Muhammadiyah as a progressive islamic movement - Nurfadhilah Paisal; Yuyun Andira Sasminto; Ansar; Asbar Sakti; Dahlan Lama Bawa (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2025)
The Progressive Islamic Movement represents the ideological and theological paradigm of Muhammadiyah, integrating the purity of Islamic teachings with the spirit of scientific advancement, social reform, and civilizational development. In practice, Progressive Islam is manifested through the movement of da’wah amar ma’ruf nahi munkar), educational modernization, social services, and community empowerment. The implementation of this concept is evident in various Muhammadiyah charitable efforts in education, health, and socio-economic sectors, all managed professionally and inclusively.